PENGARUH ABU SEKAM SEBAGAI PENGGANTI SEBAGIAN SEMEN PORTLAND TERHADAP KUAT TEKAN, KUAT BELAH DAN KARAKTERISTIK BETON - Djaka Suhirkam; Muhammad Salam Bangsawan; Robinson Martianus Silalahi; Lina Flaviana Tilik (Politeknik Negeri Sriwijaya, 2022)
Currently, research has developed that uses various kinds of additives to improve the quality of concrete, which is of higher quality, but also increases the economic cost of building a construction. This research is a mixture of cement and rice husk ash which is expected to increase the compressive strength of concrete and increase the flexural strength of the concrete. The process of processing husk ash is by filtering using a No. 200 filter. Variations in the percentage of husk ash to the volume of cement in the mixture are rice husk ash 5%, rice husk ash 10%, rice husk ash 15%. The test is carried out within 7 days, 14 days, and 28 days based on SNI 03-2491-2002. The results of this test are the optimum concrete strength value, namely normal concrete variations with an average compressive strength value of 25,078 MPa. And to produce the optimum flexural strength of concrete, normal concrete has an average flexural strength value of 4.392 MPa. So, the results of the research on the compressive strength and flexural strength of concrete with the use of rice husk ash as a cement substitute are lower than normal concrete.